(untitled) (JOURNAL OF ADVANCES IN AGRICULTURE, 2019)
Pot ornamental plant productivity is related to the environmental growth facilities but negatively affected by the pot root restriction syndrome so during nursery as the post-transplant stage. The physiological mechanism involved included both the synthesis and translocation of auxins and cytokinins. However, clear sink-source and dose-response relationships of exogenous plant regulators such as indole acetic acid (AIA) and benzyl amino purine (BAP) and environment on biomass accumulation in most ornamental foliage plants, including New Guinea Impatiens (Impatiens hawkeri) are lacking. The aim of this work was to analyze the effects of an exogenously shoot-applied auxin and a cytokinin, separately or successively, on the post-transplant biomass accumulation of I. hawkeri through the anatomical, morphological and physiological changes observed. Two experiments were performed. The first experiment included the response to only BAP-sprayed plants (0, 5, 50, or 100 mg L-1). For the second experiment, rooting cuttings of I. hawkeri were sprayed with different concentrations of IAA (0, 5, 50, or 100 mg L-1) followed by different BAP concentrations (0, 5, 50, or 100 mg L-1) one week later to run-off at sunset. Results showed that (a) a single BAP or AIA dose increased increase post-transplant biomass accumulation through a higher leaf area expansion and photo assimilate production, (b) as a result of both AIA and BAP spray, the higher NAR the higher post-transplant biomass accumulation, (c) leaf anatomical changes (leaf thickness, intercellular spaces) let a higher carbon dioxide diffusion and fixation with a correlative increase in photo assimilates, (d) a higher root system would be related to a higher cytokinin synthesis. In summary, similarities between responses to either hormone, together with the lack of any IAA - BAP interaction, provide two independent routes for commercial growers to increase the productivity of I. hawkeri ornamental plants by using early foliar sprays.